Community Response to Acute Kidney Injury Due to Children's Syrup Preparations - Didiek Hardiyanto Soegiantoro (PT Inovasi Pratama Internasional, 2023)
The mortality rate for children with a diagnosis of acute kidney injury after consuming syrup preparations in Indonesia is very high. The number of syrup preparations in Indonesia found to be contaminated with Ethylene glycol (EG) or Diethylene glycol (DEG) reached 116 syrup products. There are three issues that will be investigated as a result of the contaminated syrup: (1) the public response to the policies and responsibilities of regulators (the Indonesian Ministry of Health and the Food and Drug Monitoring Agency (BPOM), (2) the public response to pharmacies in delivering safe medicines to patients, and (3) the public response to pharmacists who are responsible for the practice of pharmaceutical services in pharmacies. This research method is a qualitative descriptive study using a Google form questionnaire which is analyzed using the Guttman scale. The questionnaire meets the qualifications in testing the validity, reliability and normality of research data. The results showed that the level of public trust in the government (Ministry of Health and BPOM) was low, while the level of trust in pharmaceutical facilities at pharmacies and pharmacists was still quite above average.